From Qitāl to Moral Transformation: A Genealogy of War Verse Interpretations in Qur’anic Exegetical History - Has, Muhammad Hasdin; Abu Bakar, Achmad; Safrudin, Moh.; Amir, Abdul Muiz (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
This study explores the transformation of the concept of qitāl within the historical discourse of Qur’anic exegesis, particularly in relation to verses often associated with warfare. The issue has gained increasing relevance in the context of Islamophobia and widespread misconceptions that frequently link Islam to violence. By employing a genealogical approach to Qur’anic exegesis, this research aims to trace the transformation of the meaning of qitāl from the pre-Qur’anic era to contemporary exegesis. The findings reveal that while qitāl initially referred to physical combat with a brutal connotation, it evolved into a concept imbued with moral and spiritual dimensions within Islamic teachings. This shift continued across the exegetical discourse from the classical to contemporary periods, where qitāl no longer solely emphasizes physical warfare but encompasses non-physical struggles that contribute to discussions on social justice and global peace. This transformation has been shaped by various social and political contexts, as well as by the agents involved. These influences indicate an ongoing dynamism in Qur’anic interpretation, reflecting its adaptation to global developments, particularly in response to Islamophobia and the narratives that associate Islam with violence.